PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK ELEKTRONIK BERBASIS PROBLEM BASED LEARNING BERBANTUAN DESMOS PADA MATERI FUNGSI KUADRAT UNTUK KELAS X SMA - Maika, Yunisa; Tasman, Fridgo (Jurnal Edukasi dan Penelitian Matematika, 2024)
The purpose of this research is to develop electronic student worksheets based on the problem-based learning model assisted by desmos on quadratic function material that is valid and practical. This type of research is research and development (R&D). The development model used is the Plomp model. The results of validity data analysis, E-LKPD developed has an average validity value of 86.45% with a very valid category. And the results of the practicality data analysis, the E-LKPD developed has an average practicality value of 95.14% with a very practical category. So it can be concluded that E-LKPD based on problem-based learning assisted by desmos on quadratic function material for class X SMA can be categorized as valid and practical. Keywords– Elektronic Student Worksheets, Problem Based Learning, Desmos, Quadratic Function